(3cJGH Gdabjg hGdeJabgs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3MOKfG eYeQ hbGd GdJejej Yf GHf YHGS Yf GdfHj Udi Gddg Ydjg hSde ai MOjK GdLhgQj Yf YHO Gddg Hf YHGS Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B: ( (3ef jQO Gddg Hg NjQkG jabgg ai GdOjf(B) s
(3BNQgG (B:s
(3JfJgi HChd QLhY GdeaJi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1447s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3CUhd Gdabgs